The notion of incarnation in the Qur’én?: a critical evaluation of Kenneth Cragg’s assertion - Muhammad, AkiluAliyu; Mohd. Daud, Noor Amali (Faculty of Contemporary Islamic Studies, Universiti Sultan Zainal Abidin (UniSZA), 2016)
Although Islam and Christianity differ on the doctrine of Incarnation, whereby Islam rejects it completely, and Christianity affirms it uncompromisingly, one of the celebrated orientalists, Kenneth Cragg, claimed to find it in the Quranic text. His main point of argument is Quran (33.56) where he asserts that the word Tasliyah shares the same notion with Christian Incarnation. This research analyzed and evaluated his argument from the Islamic viewpoint. The researchers, while using analytical and evaluative methods, argued that these two issues are incompatible and that there is no, in any way, divinity in the person of Muhammad (p.b.u.h).